THE EFFECT OF CORPORATE DIVERSIFICATION ON COMPANY PERFORMANCE USING MANAGERIAL OWNERSHIP AS A MODERATING VARIABLE - Dewi Sukmasari; Nova Berliana; Susi Sarumpaet (TECHNOBIZ : International Journal of Business, 2022)
This research conducted to analyze the effect of corporate diversification on company performance. Using product and geographic diversification as the form of corporate diversification in the manufacturing company that listed on Indonesia Stock Exchange for the period 2016-2019, this study examines effect of managerial ownership  as a the moderating variable between corporate diversification and company performance. The empirical results indicate that product and geographic diversification show insignificant and positive effect on company performance. Furthermore, managerial ownership shows significant and negative effect between product diversification and company performance. However, managerial ownership shows positive significant effect between geographic diversification and company performance.